Yield Surfaces and Criteria of Plastic Yielding for a Strain Hardening Material. Part 2. Theoretical Analysis - Miastkowski, J.; Szczebiot, R. (Engineering Transactions, 2001)
The paper presents the experimental verification of the generalized Mróz hardening hypothesis under the conditions of complex state of stress. The analysis performed takes into account the changes in size and position in the stress space of the triaxial ellipsoid illustrating the Huber-Mises-Hencky yield condition for the plane state of stress under definite plastic strains.